Thermal ablation combined with percutaneous injection of amphotericin B for the treatment of chronic pulmonary aspergillosis: a case series - Liu, Xiaofeng; Nan, Fuyao; An, Peng; Deng, Kangli; Li, Lei; Wang, Hongwu (Frontiers in Medicine, 2025)
ObjectiveTo explore the efficacy of thermal ablation combined with percutaneous injection of amphotericin B in the treatment of chronic pulmonary aspergillosis.Case reportsCase 1 was a 66-year-old female, whose computed tomography (CT) showed a space-occupying lesion in the upper lobe of the right lung. Case 2 was a 48-year-old female, and her CT scan revealed an eccentric cavity in the upper right lung accompanied by the formation of an aspergilloma. Case 3 was a 40-year-old male, and his CT indicated the formation of an aspergilloma within the cavity in the upper lobe of the left lung. All three patients had a history of pulmonary tuberculosis and were diagnosed with pulmonary aspergillosis in other hospitals. Due to the unsatisfactory effect of oral triazole drugs, they finally came to our hospital to receive the treatment of thermal ablation combined with percutaneous injection of amphotericin B. They recovered well after the operation without significant complications.ResultsDuring the follow-up period ranging from 1 month to 2 years after discharge, the patients reported no discomfort symptoms such as hemoptysis or chest pain. CT scans showed that the lesions were stable and even absorbed compared with those before treatment. The patients recovered well.ConclusionThe combination of thermal ablation and percutaneous injection of amphotericin B in the treatment of chronic pulmonary aspergillosis can significantly improve the clinical symptoms of patients and enhance their quality of life. It may become a treatment method for chronic pulmonary aspergillosis.